Transcription activation of two clusters for exopolysaccharide biosynthesis by phosphorylated DctD in Vibrio vulnificus. (28th June 2021) - Kang, Sebin; Park, Hana; Lee, Kyung‐Jo; Lee, Kyu‐Ho
Summary: NtrC‐mediated production of exopolysaccharides (EPS), essential components for Vibrio vulnificus biofilms, is highly increased in the presence of dicarboxylic or tricarboxylic acids. Gel‐shift assays showed that regulation of the EPS‐gene cluster I (EPS‐I cluster) by NtrC was direct via binding of phosphorylated NtrC (p‐NtrC) to the regulatory region of the EPS‐I cluster. In contrast, p‐NtrC did not bind to the EPS‐II and EPS‐III clusters, suggesting that NtrC regulation was not direct and another transcription factor belonging to an NtrC‐regulon might play a role in activating their transcription. A candidate transcription factor, DctD, of which expression was induced by NtrC, activated the expression of the EPS‐II and EPS‐III clusters via direct binding to their upstream regions. Under growth conditions with either dicarboxylic or tricarboxylic acids, the expression of NtrC was induced and the transcription of dctD was activated. Furthermore, DctD exhibited higher transcriptional activity under the conditions with dicarboxylic acids than with tricarboxylic acids. Therefore, this study demonstrates that under dicarboxylate‐rich conditions, both the abundance and activity of DctD were markedly induced, which activates the expression of two EPS clusters to maximize biosynthesis of EPS facilitating biofilm maturation in V . vulnificus .